Determinants of Smartphone Repeat Purchase Intention among Malaysians: A Moderation Role of Social Influence and a Mediating Effect of Consumer Satisfaction - Goh, See Kwong; Jiang, Nan; Abdul Hak, Muhamad Faiz; Tee, Pei Leng (International Review of Management and Marketing, 2016)
The purpose of this research is to examine impact of consumer inertia and product attribute on consumer intention of repeat purchase. This paper also aims to assess the medication effect of satisfaction on relation between product attribute and repeat purchase intention. This research intends to valid a moderator role of social influence impacting the association between consumer inertia and repeat purchase intention. This quantitative study proposed a conceptual framework and collected a total of 220 samples from Malaysian consumers to assess research hypothesis and construct associated relationships and impacts among several critical variables. Both measurement model and construct model were established and evaluated using AMOS 21. Results present that product attribute and consumer inertia significantly influence consumer intention of repeat purchase. Satisfaction partially mediates the relationship between product attribute and repeat purchase intention. The moderator role of social influence interacts with consumer inertia to have an impact on the level of the repeat purchase intention. Keywords: Repeat purchase intention, consumer inertia, product attribute, satisfaction, and social influence. JEL Classification: M1